Live birth after ovarian tissue autotransplantation following overnight transportation before cryopreservation - Dittrich, Ralf; Montag, Markus (Fertility and sterility, 2012)
Objective: To describe the first live birth after transplantation of ovarian tissue following overnight transportation of the tissue before freezing. Design: Technical note. Setting: University department of obstetrics and gynecology. Patient(s): A 25-year-old cancer survivor with previous Hodgkin disease and relapse. Intervention(s): The ovarian tissue was kept cool for >20 hours in a special transport medium and a special cooling device before it was cryopreserved. After premature ovarian failure due to preconditioning chemotherapy for bone marrow transplantation, the cryopreserved ovarian tissue was transplanted orthotopically. Main Outcome Measure(s): Resumption of ovarian function after transplantation, recovery of fertility, and pregnancy. Result(s): Ovarian function returned in the patient 3 months after transplantation, as shown by follicle development and estrogen production. During the fifth menstrual cycle, mild stimulation with FSH was initiated in accordance with a low-dose protocol. When ultrasonography revealed a follicle 18-20 mm in size in the ovarian graft, hCG was added and the patient had sexual intercourse at the optimal time point. On day 14 of the luteal phase, hCG concentration and vaginal echography confirmed a viable intrauterine pregnancy, which resulted in a healthy live birth. Conclusion(s): Overnight transportation of ovarian tissue appears to be possible in combination with appropriate transportation logistics. However, further investigations are needed before this procedure can be offered as a chance for women to preserve fertility independently of direct access to a tissue-processing bank.